Factors influencing youth motivation in the labour market based on own research - Bartczak, Magdalena; Szymankowska, Agnieszka (Czynniki wpływające na motywację młodzieży na rynku pracy przygotowane na podstawie badań własnych, 2019)
The situation in the Polish labour market, in which employers face lower supply of employees and their low efficiency, requires them to take actions aimed at the specific motivation of employees. They have different expectations, which are conditioned by their age, among other things. The research goal was to recognize the motivational expectations of young people on the labour market. The study included students of selected universities from the Wielkopolskie Voivodeship, and the respondents were provided with paper questionnaires to complete. The conducted research proved that young people are positively oriented towards professional challenges and to taking up employment. Although remuneration, bonuses and other financial conditions are important to them, the relationships between people, the respect and the atmosphere prevailing in the company are crucial. These expectations are certainly a challenge for modern entrepreneurs who should modify their employee motivation systems
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 129-140
Keywords: youth; motivation; work; labour market; młodzież; motywacja; praca; rynek pracy